PERAN GURU MELATIH KEMANDIRIAN ANAK USIA 5-6 TAHUN DI TK BRUDER MELATI PONTIANAK - Rika Adriana; Marmawi Marmawi; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the role of teachers as mentors, motivators and facilitators in training children's independence at the age of 5-6 years at Kindergarten Bruder Melati Pontianak. The form of research used is qualitative research, data obtained from two sources, namely human data sources (3 teachers) and documentation data sources. The method used in this research is descriptive analysis method with a qualitative approach and the type of research is case study. The results of the study show that (1) Teachers can fulfill their role as mentors by communicating learning, building good relationships with students and participating in games. (2) Providing mental stimulation by encouraging, appreciating and giving praise to students is the role of the teacher as a motivator in learning. The teacher makes daily lesson plans, carries out activities, conducts assessments and evaluations of the process and student achievement shows variable indicators, provides facilities for train children's independence in the role of the teacher as a facilitator.